2010
DOI: 10.3109/09637486.2010.523416
|View full text |Cite
|
Sign up to set email alerts
|

The food additives inulin and stevioside counteract oxidative stress

Abstract: Prebiotics such as inulin (Inu)-type fructans and alternative natural sweeteners such as stevioside (Ste) become more popular as food ingredients. Evidence is accumulating that carbohydrates and carbohydrate-containing biomolecules can be considered true antioxidants, capable of scavenging reactive oxygen species (ROS). Here, we report on the ROS scavenging abilities of Inu and Ste in comparison with other sugars, sugar derivatives and arbutin. It is found that Inu and Ste are superior scavengers of both hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 59 publications
5
126
0
6
Order By: Relevance
“…There have been continuous efforts in improving the functional performance of probiotics in gastro-intestinal tract using dietary ingredients known as prebiotics. These are non digestible ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of bacteria in colon that can improve host health (Gibson and Roberfroid 1995;Liong 2008;Stoyanova et al 2010). Non-digestible carbohydrates, oligo-and poly-saccharides, occur naturally and meet the criteria of prebiotics (Ziemer and Gibson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There have been continuous efforts in improving the functional performance of probiotics in gastro-intestinal tract using dietary ingredients known as prebiotics. These are non digestible ingredients that beneficially affect the host by selectively stimulating the growth and/or activity of bacteria in colon that can improve host health (Gibson and Roberfroid 1995;Liong 2008;Stoyanova et al 2010). Non-digestible carbohydrates, oligo-and poly-saccharides, occur naturally and meet the criteria of prebiotics (Ziemer and Gibson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of the in vitro experiment suggests that the presence of oxidized oligosaccharides could be diagnostic for ROS scavenging activity in planta. Prior experiments (Stoyanova et al, 2011) have shown that inulin polysaccharides and 1-kestose are efficient ROS scavenging molecules. Inulin is a more effective scavenger than a number of phenolic compounds .…”
Section: The Direct Participation Of Oligosaccharides In Ros Detoxifimentioning
confidence: 99%
“…Hydroxyl radical antioxidant capacities were 9 characterized by amounts of plant samples needed to decrease HTPA fluorescence (315 nm excitation, 420 nm emission) by 50% as described earlier (Stoyanova et al 2011) and were given as µM ethanol equivalent mg -1 leaf fresh weight.…”
Section: Determination Of Hydroxyl Radical Neutralizing Capacitymentioning
confidence: 99%